2004
DOI: 10.1111/j.1365-2222.2004.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum surfactant protein D is elevated in allergic patients

Abstract: We propose that serum SP-D concentrations are associated with allergic bronchial inflammation and may give additional information, beside BHR and sputum eosinophils, about the degree of bronchial inflammation in allergic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 42 publications
1
41
0
5
Order By: Relevance
“…In contrast, serum SP-D concentrations in the asthmatic patients were low, which is in accordance with data by KOOPMANS et al [28] Interestingly, the serum SP-D concentrations subsequently decreased and showed a significant correlation with urinary 9a,11bPGF 2 concentrations in the EAA patients. Serum SP-D is a biomarker of ILD activity [12] and SP-D plays a protective role in pulmonary inflammation [13].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, serum SP-D concentrations in the asthmatic patients were low, which is in accordance with data by KOOPMANS et al [28] Interestingly, the serum SP-D concentrations subsequently decreased and showed a significant correlation with urinary 9a,11bPGF 2 concentrations in the EAA patients. Serum SP-D is a biomarker of ILD activity [12] and SP-D plays a protective role in pulmonary inflammation [13].…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies indicated significant changes in levels of SP-D during asthmatic inflammation of the lung in animal models (19 -21) as well as in asthmatic patients (22,23). We previously described that SP-D is selectively increased among the SPs following allergen challenge of sensitized mice (24,25).…”
mentioning
confidence: 92%
“…The involvement of pulmonary surfactant in the pathophysiology of asthma has been suggested [1][2][3][4]. An interesting working hypothesis is that the surface tension of the peripheral airways is altered in asthma, because the inflammatory process affects the structure and function of surfactant, leading to excessive airway narrowing and features of air trapping.…”
Section: To the Editormentioning
confidence: 99%